The Role of Nutrition Education in Reducing Obesity Rates in Elementary School Children: A Policy Review - Yusnika Damayanti; Ertati Suarni; Herlina Lidiyawati; Eny Retna Ambarwati; Endang Werdyaningsih (Universitas Ibn Khaldun Bogor, 2026)
Obesity in primary school-age children is a growing public health challenge and requires integrated policies to reduce its prevalence. Schools have a strategic role in shaping healthy eating behaviors and lifestyles through planned and sustainable nutrition education. This study aims to map the role of nutrition education in supporting the reduction of obesity rates among elementary school-age children through content analysis of international and national policy documents, as well as identifying obstacles and opportunities for its implementation. The qualitative content analysis approach was used on seven official documents from WHO, FAO, UNICEF, CDC, and the Ministry of Education and Culture-UNICEF Indonesia. The results of the study show that nutrition education plays an important role in improving children's knowledge, attitudes, and healthy eating behaviors, and has the potential to support reducing the risk of obesity when integrated with school environmental policies such as healthy canteens, scheduled physical activities, and cross-sectoral support. However, its effectiveness is still hampered by limited teacher capacity, resources, and intersectoral coordination. The study does not quantitatively measure the reduction in obesity, but highlights the contribution of nutrition education and school policies in efforts to reduce the risk of childhood obesity in a sustainable manner.